PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN JASA KARGO DI BANDARA JUWATA TARAKAN - Indy Harpas Sari; Laisa Liza (Lembaga Riset dan Inovasi Kreyat Center, 2023)
The Tpurpose Tof Tthis Tstudy Twas Tto Tdetermine Tthe Teffect Tof Tservice Tquality, Ttrust Tand satisfaction Ton Tcustomer Tloyalty Tfor TCargo TServices Tat TJuwata TAirport, TTarakan. The benefits Tof Tthis Tresearch Tare Trelated Tto Tincreasing Tcustomer Tloyalty Tin Tterms Tof Tservice quality, trust Tand Tcustomer Tsatisfaction. This Tstudy Tuses Ta Tquantitative Tresearch approach, where Tthe Tobject Tof Tthis Tresearch Tis Tin TCargo TServices Tat TJuwata TTarakan Airport Tby taking Ta Tresearch Tsample Tof T67 Trespondents. TheTanalysisTtechnique used is multiple linear. And the results of his research show that service quality affects customer loyalty at Jasa Kargo, then trust affects customer loyalty at Jasa Kargo.